Potencialidades turísticas que presenta el distrito de Chao, para el desarrollo del turismo. - Vásquez Cotrina, Jael Tamar (2018)
The present research work entitled Tourism Potentialities presented by the Chao_x000D_ District for Tourism Development; seeks to analyze, identify and evaluate tourist_x000D_ resources, tourism facilities, tourist infrastructure and community of the Chao_x000D_ District, Virú Province, La Libertad Region, developed within the framework of the_x000D_ methodological procedure established in the Manual for the Formulation of the_x000D_ Inventory of Tourist Resources at the National Level of the Ministry of Foreign_x000D_ Trade and Tourism - MINCETUR._x000D_ A total of 11 tourist resources have been registered, of which 07 are resources in_x000D_ operation and 04 are not in operation. In the Natural Sites category, the district has_x000D_ 4 tourist resources, while in the Cultural Manifestations category there were 3_x000D_ tourist resources. In the folklore category we have 02 tourism resources. As for the_x000D_ Programmed Events Category, we find 02 tourist resources being the party in_x000D_ honor of the Virgen of Carmen and the party of the Chao district. Not only are the_x000D_ potential tourist resources for tourism development in the District, there is also the_x000D_ tourist facility; that is, the tourist establishments as lodging services; where 5_x000D_ establishments were registered able to render a good service for the visitors of the_x000D_ District of Chao. As for the food service; there were 3 establishments that have a_x000D_ service able to meet the needs of the visitor.VI_x000D_ As for the transport service. Another potential is the tourist infrastructure as well as_x000D_ access roads and basic services. And as the last potential is the community of_x000D_ Chao District, who are willing to support with tourism development._x000D_ For this it was necessary to use the categorization and hierarchization phases; the_x000D_ categorization phase has made it possible to know tourist resources in a real and_x000D_ orderly way, as well as to collect information and categorize them into Natural_x000D_ Sites, Cultural Manifestations, Folklore and Programmed Events; while the_x000D_ hierarchization phase consists of determining the weighting of each resource and_x000D_ in this way determining the inclusion for the use of the resource in the tourism_x000D_ development of it._x000D_ Within the research methodology that was used is the Analytical - Synthetic_x000D_ Method; by means of this method the variables were analyzed individually; also the_x000D_ Ethnographic Methodology; this methodology was used in the field stage, which_x000D_ allowed describing the tourist elements that the Chao District has. To determine_x000D_ the number of population studied, the finite population formula was applied, which_x000D_ resulted in 186 economically active people._x000D_ The Chao District does have tourism potential for the development of tourism._x000D_ Because it has enough tourist resources, not only that; It also has a tourist facility,_x000D_ tourist infrastructure and finally the community, who with their kindness and_x000D_ dedication are willing to work for the District's tourism development.